New model for predicting terminal settling velocity and drag coefficient of the Oncomelania - Liu, Xiaoguang; Wang, Jiasheng; Chai, Zhaohui; Min, Fengyang; Jiang, Xi; Zhu, Kongxian; Dai, Juan (Frontiers in Environmental Science, 2022)
This paper presents a study of the terminal settling velocity and drag coefficient of the Oncomelanias with highly irregular shape in the range of particle Reynolds number (10